S88 Neutrophil elastase increases ciliary beat frequency ex-vivo: implications for the bronchiectasis airway. (December 2018) - Shoemark, A; Contarini, M; Giam, YH; Keir, HR; Cassidy, D; Chalmers, JD
Abstract : The neutrophil derived protease, Neutrophil elastase (NE), in patient sputum is a biomarker of bronchiectasis severity. The vicious cycle of bronchiectasis pathogenesis suggests NE reduces ciliary beat frequency (CBF), compromising mucociliary clearance. Early studies assessing high concentration porcine elastase or patient sputum on CBF confirmed this hypothesis. The aim of this study was to investigate the effect of physiological NE concentrations on nasal cilia with the hypothesis that NE inhibitors may be a target for improving mucociliary clearance in bronchiectasis. Nasal brushing was performed on healthy volunteers (free from respiratory infections for at least 5 weeks). CBF of nasal epithelial cells evaluated by high-speed video light microscopy immediately in suspension and following culture at air liquid interface (ALI). Media/buffer alone or NE (0.1 U/ml)±NE inhibitor (AZD9668, 10 nM) were added and CBF calculated at 37°C. A cohort of 10 volunteers (mean age: 29.2 years; males: 40%; 100% non smokers) was selected. The mean (SD) of all CBF measurements from nasal epithelial cells in suspension was 13.83 (3.46) Hz, with a significant increase after NE exposure (12.5% (95% CI 11.3% to 13.6%), p<0.0001). Addition of NE to the apical surface of ALI cultures also resulted in increased CBF (15.0% (4.3%–25.1%) n=5 p=0.01) suggesting presence of NE at the airway surface increases CBF. The CBF increase occurred within 5 min and persisted beyond 72 hours. The increase of CBF was not reversible by washing with media (2.5%, p=0.5) or the subsequent addition of NE inhibitors (7%, p=0.4). Ciliated cells pre-treated with NE inhibitor showed no significant increase in CBF (3.5%, p=0.4), suggesting the increase is mediated by the protease action of NE. In conclusion, NE, at concentrations present in bronchiectasis sputum, increase CBF. The cause of reduced CBF in bronchiectasis airways and the role of NE in mucociliary clearance require review.